行動功能指標「日常生活功能」及「工具性日常生活功能」預測台灣老年人跌倒風險之探討 - 鄭秀瑮(Hsiu-Li Cheng); 蔡仲弘(Alan C. Tsai) (台灣公共衛生雜誌, 2012)
Objectives: To determine the association between functional ability as indicated by ADLs (Activities of Daily Living) and IADLs (Instrumental Activities of Daily Living) and the risk of falling in older Taiwanese. Methods: Data were drawn from the 2003 and 2007 datasets of ”The Survey of Health and Living Status of the Elderly in Taiwan”. Subjects were 3778 participants who completed both surveys. Logistic regression analysis was employed to determine the association of ADL and IADL status with the risk of falling in 2003 and 2007 after controlling for demographic, lifestyle and health-related variables. Results: In cross-sectional analysis, IADLs but not ADLs were significantly associated with the risk of falling during the prior year. Those who had 1-2, 3-4 or 5-6 dependencies in 2007 had 1.49 (1.17-1.89, p＜0.001), 1.71 (1.20-2.25, p＜0.003) and 2.10 (1.31-3.38, p＜0.002) times the risk of falling, respectively, during the previous 12 months when compared to those who had no dependency. Mild (1-2 dependencies